Analysis Of Selected Antibiotics And Heavy Metals In Northern Malaysia Sewage Treatment Facilities Using A Wastewater Based Epidemiology Approach - Ruzi, Iqbal Iman (2023)
The purpose of this study was to analyse the presence and the fate of four (4) selected last-resort antibiotics (Colistin, Polymyxin B, Meropenem, and Vancomycin) with the additional five (5) selected heavy metals (Copper, Cadmium, Nickel, Zinc, and Iron) in wastewater samples from 18 different sewage treatment plants (STP) in the northern part of Malaysia.